Callogenesis and somatic embryogenesis of Moroccan saffron (Crocus sativus L.), effect of disinfection and hormonal treatments - Soukaina ABOU-WAKIL; Fatima HOUSTI; Mohamed ROCHD (Notulae Scientia Biologicae)
The saffron (Crocus sativus L.) propagation is limited by the low multiplication rate of corms in the fields besides the problem of their infestation by pathogens. Somatic embryogenesis is one of the techniques that offers great potential for production of healthy corms and large-scale propagation of saffron. In this investigation, saffron corms from Meknes region (in north-west of Morocco) were used as source of explants. The effect of various disinfection protocols containing mercuric chloride or potassium permanganate and hormonal combinations on explants contamination rate, callogenesis, coloration, browning and capacity to produce somatic embryos during culture were evaluated. The results showed that the highest concentrations of mercuric chloride (0.6 and 1%) allowed respectively effective disinfection (6% and 0% contamination); however, they inhibited the development of the explants. The potassium permanganate at 0.1% reduced contamination to 14% but also reduced the percentage of callus induction and their embryogenic potential. The highest rate of callus induction (96%) and embryo formation (81%) were obtained with Murashige and Skoog medium supplemented with 1.0 mg L-1 2,4-dichlorophenoxyacetic acid and 1.0 mg L-1 kinetin. The different colorations of saffron callus observed which evolved during the advancement of cultures ages were influenced by growth regulators and disinfection methods. In fact, disinfection protocols or hormonal combinations that promoted callus induction and embryo formation presented lower browning and higher percentage of whitish orange callus.